REVIEW OF SOFTWARES USED IN CONSTRUCTION INDUSTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The use of software and information technology in every field has been growing since last two decades. Earlier softwares were used to be effective in designing field only, later on integration of different modules of business made industries to focus on other relevant applications of softwares. This led to innovation of new softwares for underrated domains of industry such as construction management etc. The paper reviews various softwares used in the construction industry across globe. Special focus is on project planning of various construction types.